Exploring risk transfer of human brucellosis in the context of livestock agriculture transition: A case study in Shaanxi, China - An, Cuihong; Shen, Li; Sun, Minghao; Sun, Yangxin; Fan, Suoping; Zhao, Chenxi; Nie, Shoumin; Luo, Boyan; Fu, Ting; Liu, Kun; Shao, Zhongjun; Chang, WenHui (Frontiers in Public Health, 2023)
As one of the re-emerging zoonotic diseases resulted from worldwide agricultural intensification, brucellosis has become an increasing challenge for global public health. However, existing and future uncertainties in identifying the risk transfer of human brucellosis (HB) will definitely have a significant effect on the relevant scientific researches. This study attempted to explore the risk transfer of HB between the exact epidemic areas and the neighboring or distant low-risk areas to explain the impact of livestock agriculture intensification and foodborne infection on the transmission of HB in Shaanxi Province as a case study. We comparatively adopted multiple approaches including Test-based methods, Model-based methods and Geographical Detector to spatial-temporally detect the dynamic changes of high-risk epidemic areas of HB at county scale. We also quantitatively measured how the related factors drove the risk transfer of the disease. Results confirmed that the risk transfer pattern of HB with an expansion from north to south in Shaanxi Province and found two primary transfer routes. In particular, in the traditional epidemic area of Shaanbei plateau, farm agglomeration effect can significantly increase the risk of HB to some extent. Meanwhile, retail outlets for milk and dairy products were partially responsible for the foodborne infection of HB in the new epidemic area of Xi’an. The current study not only contributed helpful insights to support HB control and prevention in the rapid transition of livestock agriculture, but also provided possible solutions and directions for further research on foodborne HB infection caused by unpasteurized products in urbanized areas.